Research Impact Publication of the Research Center for Conservation of Marine and Inland Water Resources (Research Impact Publikasi Pusat Riset Konservasi Sumber Daya Laut dan Perairan Darat) - Grahita, Davina (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
Research publications owned by an organization, institution or research centre are related to metrics, research metrics and research impact. The purpose of this study is to determine the research impact of the Research Center for Conservation of Marine Resources and Inland Waters using bibliometric analysis. The results of the discussion in this study show that Vitas Atmadi Prakoso is the author who has the most scientific publications with 29 works. Meanwhile, Hadiwijaya Lesmana Salim is a writer with 135 citations. The most cited article with 190 citations, was written by Matthew J. Neave et al., in 2017. Then, the IOP Conference Series: Earth and Environmental Science Journal has the most research publications of 113 publications with a total of 234 citations. Then, out of 39 countries in the collaboration network, there are only 9 countries that meet the specified threshold. In addition, the keywords often used are aquaculture, coastal zones, ecology, ecosystems, and fish, with keywords in the title based on the word cloud being Indonesia, fish, fisheries, water quality, and biodiversity.